Intraoperative Pontine Infarction: A Hidden Challenge - Nicholas Marcanthony; Ehab Farag (Case Reports in Anesthesiology)
Apneusis, or apneustic respirations, is characterized by an abnormal breathing pattern involving gasping and the inability to fully expire. A loss of gag reflex and other cranial nerve deficits are also often accompanied with these respiratory changes. In neurological intensive care units (NICUs), these respiratory and airway changes are not uncommon and have been well documented (Lee et al. 1976). These clinical changes are often associated with pontine trauma as it is the core pneumotaxic center in the brain stem. We describe the airway management of a patient with an acute, occult pontine infarct status post craniectomy and cervical laminectomy for decompression of known Chiari malformation in the postanesthesia care unit (PACU).